Normative influences on young drivers' illegal smartphone use: Applying an extended Theory of Normative Social Behaviour. (February 2023) - Gauld, Cassandra; Reeves, Caitlin
Highlights: A range of norms influence young drivers' illegal smartphone use. Subjective norm moderates the relationship between descriptive norm and intention. Subjective norm, injunctive norm, and outcome expectancies are partial mediators. The extended Theory of Normative Social Behaviour was partially supported. Abstract: In the 12 months to November 2021, 19 % of the people killed on Australian roads were aged between 17 and 25 years, despite this age group making up just 12 % of the driving population. A substantial number of these crashes resulted from smartphone use. It is widely accepted that norms influence young drivers' smartphone use; however, there is a dearth of research investigating how different norms interact to influence this behaviour. The current survey study ( N = 137) applied an extended Theory of Normative Social Behaviour (TNSB) to investigate illegal smartphone use among young drivers. The original TNSB model proposes that injunctive norm (i.e., perceived societal approval), outcome expectancies, and group identity each moderate the relationship between descriptive norm and behavioural intention. The current study added subjective norm (i.e., perceived approval from important others) to the model. Moderation analyses found that only subjective norm moderated the relationship between descriptive norm and behavioural intention, whereas subjective norm, injunctive norm, and outcome expectancies each partially mediated this relationship. These findings provided partial support for the TNSB. They highlighted the influence of a range of norms on young drivers' smartphone use (i.e., descriptive norm, subjective norm, and injunctive norm) and, in particular, the influence of subjective norm in this context. It also highlights the importance of investigating how norms interact with each other to influence the relationship between descriptive norm and behavioural intention. In accordance with these findings, future public education messages should challenge normative influences, and subjective norm in particular, on young drivers' smartphone use.